The impact of political risk on imports in Malaysia / Noor Zahirah Mohd Sidek, Azlina Hanif - Hanif, Azlina (Faculty of Business and Management, 2013)
This paper examines the impact of political risks on imports in Malaysia. A wide array of indicators for political risk is used to examine their relative importance on imports. The paper uses Fully-modified OLS regression technique and the findings reveal that several types of indicators namely socio-economic conditions, law and order, religion in politics, democratic accountability and bureaucracy quality seem to exert significant impact towards imports in Malaysia. The impact however, is relatively small. An important policy implication is that policy makers should account for political risks apart from other institutional risks such as the conventional economic and financial risks in the formulation of trade policies